2004
DOI: 10.1002/chin.200419134
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐Assisted Free Radical Chemistry Using the Persistent Radical Effect.

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Later, the synthesis was improved by ionic Horner–Wadsworth–Emmons-type olefination reaction under microwave (MW)-induced heating to generate α, β-unsaturated oxindoles. Interestingly, using MW irradiation, a 430-fold acceleration was achieved upon switching from classical heating to MW-induced heating . Later on, steric effects in the nitroxide moiety on the outcome of the PRE-mediated radical alkoxyamine isomerization and intermolecular addition reaction were demonstrated …”
Section: Tempo In Chemical Transformationmentioning
confidence: 99%
“…Later, the synthesis was improved by ionic Horner–Wadsworth–Emmons-type olefination reaction under microwave (MW)-induced heating to generate α, β-unsaturated oxindoles. Interestingly, using MW irradiation, a 430-fold acceleration was achieved upon switching from classical heating to MW-induced heating . Later on, steric effects in the nitroxide moiety on the outcome of the PRE-mediated radical alkoxyamine isomerization and intermolecular addition reaction were demonstrated …”
Section: Tempo In Chemical Transformationmentioning
confidence: 99%
“…1 ) 28 29 . However, if a persistent radical and a transient radical simultaneously exist in one reaction system, selective cross-coupling would probably occur according to the persistent radical effect 30 31 . As we know, radical species could be affected through some patterns by transition metals 32 33 , which can catalyze radical reaction 34 .…”
mentioning
confidence: 99%
“… Around the same time our group disclosed the intermolecular reaction of TEMPO–malonates with alkenes via malonyl radical addition to alkenes and subsequent trapping with TEMPO . Later it was found that such thermal alkoxyamine addition or isomerization reactions can be conveniently conducted under microwave conditions or in a flow reaction set up or be combined with a Tsuji–Trost allylation . In addition, this formal C–O bond insertion of an alkene was also applied to chemically modify surfaces or to functionalize polymers. , Gigmes and co-workers generated secondary α-carbonyl radicals from the corresponding alkoxyamines and radical addition reactions leading to monocyclic, bicyclic, spirocyclic, and 8-membered lactones and lactams …”
Section: Nitroxides In Free-radical Chemistrymentioning
confidence: 99%